Tree-Like Structures in Architecture: Revisiting Frei Otto's Branching Columns Through Parametric Tools - Selçuk, Semra Arslan; Gülle, Nur Banu; Mutlu Avinc, Güneş (Sage Publications Inc, 2022)
Tree-like architectures and branching structures are one of the analogical designs that are among the nature inspired structures arousing attention of the designers, inspiring them and that are frequently confronted throughout the history of architecture. Likewise, trees are structural models for designers beyond the plant and branching patterns that are used as architectural ornamentation. Trees have the characteristics of being mentors for architects and engineers concerning how the vertical and the horizontal loads are transmitted through the trunks, branches, and leaves and how the balance is provided. Within this context, it is possible to claim that a quite wide and intuitively developed structural knowledge is acquired with the tree analogies throughout the history of architecture. By the development of computational design technologies, there have been significant developments in the design and the building of tree-like structures. Especially the number of branching, angles of dendroids, lengths, and the other parameters can be defined by using algorithms and can be optimized also by the help of computational tools. In this paper, the historical development and classification of the treelike structures have been carried out and Frei Otto who is the pioneer to pave the way for innovative structures related to this field has been selected to revisit the efficiency of lightweight columns inspired by nature. One of the experimental studies of Otto in which he called as minimum path system has been determined as the case study; the parametric design behind the structure has been analyzed and reproduced by using a parametric software. The structural effectiveness has been determined and discussed by testing the obtained models using a FEM program under horizontal and vertical loads. Consequently, the structural effectiveness of today's computational technologies and the branching structures that Otto built intuitively and by natural analogies have been able to be tested and the possible potentials that can be leading for today's architects have been demonstrated.
Keywords: learning from nature; nature-design relation; branching columns; tree-like structures; Frei Otto